Green Infrastructure to Develop Ecosystem Services in Synergy with Energy Transition Planning - Semeraro, Teodoro (Advanced Aspects of Engineering Research Vol. 2, 2021)
With the aim to decarbonize the economy for sustainability, specific European policies have pushed the transformation of many agricultural crops to PhotoVoltaic (PV) farms. The realization of ground-based PV farms requires suitable spaces producing several environmental impacts on landscapes and biodiversity caused by site modifications. The concept of multifunctionality integrated into landscape design is a suitable analytical framework to develop sustainability strategies of land use for renewable energies. The aim of this work is to discuss two examples of multifunctionality land-use projects in the energy transition in the Apulia Region. The study proposes a methodology to harmonize energy production and the enhancement of ecosystem services, looking for a synergy between different economic activities and stakeholders. This s the base to develop green infrastructure (GI) in the landscape producing more sustainability in energy transition planning. Different from the usual design of photovoltaic panels in farmlands, the examples reported focused on a proposal of the combination of photovoltaic panels and biodiversity and ecological functions focused on food; water, raw materials, and medicinal resources provisioning services to support economic and social needs. Moreover, this green infrastructure can improve regulations services like Air quality regulation, climate regulation, waste treatment, Maintenance of soil fertility, and Pollination to reduce the environmental impact of photovoltaic farms. Mainly, climate regulation services can improve energy production reducing temperature around the photovoltaic panels producing strong feedback in the business process. These GI can represent habitat services in the landscape supporting maintenance of life cycles of migratory species and Maintenance of genetic diversity. These projects need a new vision of environmental aspects that should not be treated only as potential impacts of human activity or as mitigation strategies, but as an active part of the photovoltaic design and, more generally, energy transition planning.